Older adults’ expectations, experiences, and preferences in programming physical robot assistance - Ajaykumar, Gopika; Pineda, Kaitlynn Taylor; Huang, Chien-Ming (International journal of human-computer studies, 2023)
Robots are expected to be key enablers in assisting older adults with aging in place by providing cognitive, social, and physical assistance. Because older adults vary greatly in terms of their needs for robot assistance, there may be potential advantages to enabling them to tailor robot assistance to work for their unique contexts through end-user robot programming. However, little is known about the feasibility and potential of engaging older adults in programming robot assistance. In this work, we explore the possibility of engaging older adults in programming physical robot assistance through field study sessions in older adults’ homes. Through interviews and observations of older adults’ programming experiences using a contemporary commercial robot programming method, we found that familiarity with other forms of automation and interactions, changes in abilities due to aging, multi-user and collaborative programming, cognitive exercise, and mental model formation can play an important role in shaping older adults’ expectations, experiences, and preferences in programming physical robot assistance. Based on these findings, we recommend guidelines to consider when designing future robot programming interactions for older adults. •Field study exploring older adults’ programming interactions with robot assistance.•Themes that shape older adults’ expectations, experiences, and preferences.•Recommendations for designing future robot programming interactions.